Factors that cause poor performance in mathematics at National School Secondary Certificate level compared to Junior Secondary Certificate level in four selected schools in the two Kavango educational regions (Journal for Studies in Humanities and Social Sciences, 2016)
This paper reports on factors that cause poor performance in Mathematics at the National School Secondary Certificate (NSSC) level compared to Junior Secondary Certificate (JSC) level. A total of 200 learners in Grade 10 (2011) and 170 Grade 12 (2013) were involved in the study. These learners did Mathematics at the same school for a period of three years (2011-2013). This study employed document analysis, a technique used to gather information by reviewing and analysed documents. In this study the following documents were reviewed and analysed: The 2011 Grade 10 November examination results, and the 2013 Grade 12 November examination results, respectively. The findings of this study revealed that 2011 Grade 10 learners who obtained E-U symbols did not perform well in the Grade 12 Mathematics examinations. These findings were of utmost importance to the curriculum developers, the National Institute for Educational Development (NIED), senior education officers, the Ministry of Education, institutions of higher learning, and other stakeholders in Mathematics education.